PENGARUH METODE SUGESTOPEDIA DALAM PEMBELAJARAN MENULIS PUISI SISWA KELAS X SMA - Nur Asmayani Tamsir; Usman Usman; Abdul Azis (Universitas Negeri Makassar, 2020)
The Influence of Suggestopedia Methods in Learning to Write Poetry in Class X High School Students. This study aims to describe the students' writing skills before applying the suggestopedia method and after applying the suggestopedia method. (3) Determine the influence of suggestopedia methods on student poetry writing learning. This type of research is a quantitative study with a pre-experimental design using test techniques, namely the initial test (pretest) and final test (posttest). The results showed that (1) the average value obtained by students before applying the suggestopedia method was sufficient. (2) The average value obtained after applying the suggestopedia (posttest) method is categorized high. (3) Suggestopedia method significantly influences the ability to write poetry.